Accelerating Assurance Document Processing in Telkom's Project Resolution Management: The Design and Implementation of the Assurance Document Acceleration Program (ADAP) - Andang Ashari; Dian Sulistyaningsih; Natasya Prima Oktaviani; Alamandari Faris; Riandi Aditia Darmayana (Research Synergy Press, 2026)
Telkom's partnership business model has generated a buildup of unbilled vendor projects. To address this, Telkom launched Project Resolution Management (PRM) in August 2024 to resolve 8,097 projects worth Rp 3.4 trillion by December 2025. Within PRM, the PSLA unit is responsible for 3,889 maintenance projects requiring 11,667 assurance documents. This research proposes the Assurance Document Acceleration Program (ADAP) as an operational intervention to accelerate document processing without compromising compliance. Fishbone Diagram, Internal Factor Evaluation (IFE), and External Factor Evaluation (EFE) methods were applied to identify root causes, finding inefficient business processes, system dependencies, and high document volume as key issues. ADAP was piloted with 9 of Telkom's highest-billed subsidiaries. Following a socialization phase (May–June 2025), the active piloting phase (July–October 2025) yielded a monthly average of 86 completed projects — a 100% increase from the pre-ADAP baseline of 43 projects per month (January–June 2025). From January to November 2025, PSLA completed 976 projects, of which 516 (52.9%) were completed under ADAP, indicating strong potential to meet the December 2025 target. This research is limited to Telkom's PRM program, specifically the PSLA unit and its assurance document completion process. The practical originality lies in the design and piloting of ADAP within Telkom's PRM context, demonstrating that streamlined documentation practices can double monthly project throughput without compromising compliance. Their combined application in a state-owned telco context offers replicable insights for similar high-volume document backlogs in large organizations.